Learning from Large-Scale Solar Home System Electrification in Bangladesh - World Bank (Washington, DC, 2022)
The Bangladesh Solar Home Systems (SHS) Program contributed significantly to achieving near-universal access to electricity by installing over 4 million SHSs from 2003 to 2018, serving 16 percent of rural households by 2016. The government mobilized USD 683 million in loans and grants from international development partners for roll-out financing, which leveraged an additional USD 412 million from domestic sources. The Program provided significant benefits to all participants, especially rural households. These experiences are relevant to Sub-Saharan Africa, where nearly 600 million people lack electricity access and 40 percent of electricity connections will need to be off-grid to achieve universal access by 2030